Peran Bakteri Pengikat Nitrogen dalam Meningkatkan Kesuburan Tanah dan Produktivitas Pertanian : Kajian Literatur - Waruwu, Dodi Roni Yanto; Lase, Natalia Kristiani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The use of nitrogen-fixing bacteria in agriculture is an effective way to improve soil fertility and overall crop productivity. Bacteria such as Rhizobium, Azotobacter, and Azospirillum are able to extract nitrogen from the soil and convert it into a form that can be absorbed by plants, which is essential for the formation of protein, DNA, and RNA in plants. By utilizing the capabilities of these bacteria, the use of synthetic chemical fertilizers can be varied, thereby reducing the detrimental dampening effects on water quality and the environment. In addition, nitrogen-fixing bacteria improve water use efficiency and contribute to the health of aquatic ecosystems. The use of these bacteria has the potential to improve the results of a more thorough analysis with less cost and less environmental impact.